Efficacy and safety of renal denervation in addition to pulmonary vein isolation for atrial fibrillation and hypertension—Systematic review and meta‐analysis of randomized controlled trials - Pranata, Raymond (J Arrhythm, 2020)
INTRODUCTION: This systematic review and meta‐analysis aimed to assess the latest evidence on the use of renal denervation (RDN) + pulmonary vein isolation (PVI) compared to PVI alone for treating atrial fibrillation (AF) with hypertension. METHODS: A systematic literature search from several electronic databases was performed up until January 2020. The primary outcome was AF recurrence defined as AF/atrial flutter (AFL)/atrial tachycardia (AT) ≥30 seconds at 12‐month follow‐up and the secondary outcome was procedure‐related complications. RESULTS: There were 568 subjects from five studies. AF recurrence was 90/280 (32.1%) in the RDN + PVI group and 142/274 (51.8%) in the PVI group. RDN + PVI was associated with a lower incidence of AF recurrence (RR 0.62 [0.51, 076], P < .001; I (2): 0%). Pooled analysis of HR showed that RDN + PVI was associated with reduced AF recurrence (HR 0.51 [0.38, 0.70], P < .001; I (2): 0%). Complications were 7/241 (2.9%) in the RDN + PVI group and 8/237 (3.4%) in the PVI group. The rate of complications between the groups was similar (RR 0.87 [0.33, 2.29], P = .77; I (2): 0%). In the subgroup analysis of paroxysmal AF, RDN + PVI was shown to reduce AF recurrence (RR 0.64 [0.49, 0.82], P < .001; I (2): 0% and HR 0.56 [0.38, 0.82], P = .003; I (2): 0%) compared to PVI alone. RDN + PVI has a moderate certainty of evidence in the reducing AF recurrence with an absolute reduction of 197 fewer per 1000 (from 254 fewer to 124 fewer). CONCLUSION: RDN in addition to PVI, is associated with reduced 12‐month AF recurrence and similar procedure‐related complications compared to PVI alone.